Gender Equity and Stereotype Threat in Mathematics Textbooks - Ulusoy, Fadime; Incikabi, Lutfi (IGI Global Scientific Publishing, 2025)
This study investigates gender representations in a mathematics textbook published under Turkey's 2024 revised national curriculum. Using content analysis, it explores four dimensions: the diversity and frequency of social roles, representation in profitable occupations, attitudes toward mathematics, and narratives related to the stereotype that “girls cannot do math.” The findings reveal a persistent imbalance. Males are more frequently shown and often occupy high-status, profitable, cognitively demanding roles such as scientist or entrepreneur. Females, while present as students or teachers, are largely absent from leadership or technical fields. Girls are depicted as smiling or thoughtful, yet never struggling—an idealization that masks real learning. Though the textbook includes more counter-stereotypical cases than previous ones, they remain few and shallow. Stereotypes—such as girls needing help or lacking confidence—still appear. The study calls for more equitable representations of girls in math to promote inclusion and challenge bias.